Microbial community succession in response to sludge composting efficiency and heavy metal detoxification during municipal sludge composting - Han, Weijiang; Chen, Shuona; Tan, Xiao; Li, Xin; Pan, Hua; Ma, Peijian; Wu, Zhihua; Xie, Qilai (Frontiers in Microbiology, 2022)
This study researched microbial community succession in response to sludge composting efficiency and heavy metal detoxification during municipal sludge co-composting with spent mushroom and spent bleaching. The change law of key physicochemical properties, the heavy metals contents and forms during composting were analyzed, and the passivation of heavy metals after composting was explored. High-throughput sequencing was used to analyze the microbial community structure of treat 2 during composting, and the correlation analysis of microbial community structure with heavy metal contents and forms were carried out. The results showed that the sludge of each treatment reached composting maturity after 26 days of composting. Organic matter content, electrical conductivity, pH and seed germination index of treat 2 were all in line with the standard limit of agricultural sludge. Because of the presence of compost bacteria addition, the passivating heavy metals performance of treat 2 satisfied the standard limit of agricultural sludge after composting, which was superior to that of treat 1 and treat 3. The diversity of microbial communities in treat 2 decreased during composting. Extensive bacteria such as Bacillus, Geobacter, Lactobacillus, and Pseudomonas, which possessed the abilities of heavy metal passivation and organic oxidizing, were dominant in treat 2 during the heating stage. However, as composting proceeded, Tuberibacillus with ability of organic oxidizing gradually became the most dominant species at the thermophilic and cooling stages. Changes in microbial function varied from changes of microbial community in treat 2, subsequently affected the performances of heavy metal passivation and organic oxidizing during composting.